STRATEGI BAURAN PEMASARAN PADA KANTOR BERITA ANTARA BIRO SULAWESI SELATAN - Nuhung, Mahmud (Jurnal Ekonomi Balance, 2011)
The purpose of the study to determine the effect of marketing mix strategy has to increase the sales volume of products on Perum institutions news agency BETWEEN Bureau of South Sulawesi. And to know the dominant factor of the effect on the increase of product sales volume at Perum institutions news agency BETWEEN Bureau of South Sulawesi. The result of the research concludes that together variable of production cost, cost of goods sold, distribution cost, and promotion cost have significant effect to increase of sales volume at Lembaga Berita Negara (LKBN) BETWEEN Makassar. This is evidenced from the F test value that indicates that the significance value is much smaller than alpha 0.05. This indicates that the four variables analyzed have significant predictability of predictive power.